Clinical association and visual morbidity in uveitis with systemic diseases: An analysis from a tertiary ophthalmic center - Radha Annamalai; Abhinav Mahesh; Jyotirmay Biswas (Oman Journal of Ophthalmology, 2023)
AIM: The aim of this study was to identify the incidence, etiology, most common presentations, complications, and the causes of visual loss in posterior uveitis (PU). MATERIALS AND METHODS: A retrospective study was conducted on a cohort of 125 patients with PU with a minimum follow-up of 6 months. Ocular evaluation consisted of slit-lamp examination, indirect ophthalmoscopy, tonometry, and refraction. Ancillary ophthalmic investigations such as fundus fluorescein angiography, optical coherence tomography, and B-scan ultrasonography were done. Laboratory tests were performed on blood on all patients and in aqueous humor samples obtained by anterior chamber paracentesis in cases of diagnostic dilemmas. All the data were analyzed using SPSS program. RESULTS: PU occurred in 61%. Infections were noted in 34% and autoimmune diseases in 27%. The most frequent presentation was choroiditis. The most common etiologies were tubercular uveitis in 50%, Toxoplasma retinochoroiditis in 23%, and autoimmune category of serpiginous choroiditis in 56% of patients. Complications occurred in 27% and were most commonly cystoid macular edema and macular scarring. Polymerase chain reaction (PCR), nested PCR, and real-time PCR on ocular fluids were required for diagnosis in 30%. A combination of laboratory investigations on blood and aqueous humor samples were confirmation in 88%. CONCLUSION: PU and its sequelae are known to be sight threatening and are associated with systemic diseases. They have diverse etiologies and presentations. Identification of etiology is important as management is diametrically opposite in infections and autoimmune diseases.